Frontiers of Human-Machine Teaming: How Human Factors Is Contributing. (December 2020) - Rayo, Michael F.; Rayo, Michael F.; Roth, Emilie M.; Morison, Alexander M.; Zelik, Daniel J.; Trent, Stoney A.
Although the majority of effort in Artificial Intelligence (AI) ideation, design, and development seeks to optimize the AI as the primary method of optimizing overall system performance, the evidence is clear that for risk-critical work in high-complexity, high-uncertainty settings, it is the interactions between human and machines that must be prioritized. Only be effectively coordinating the available machine and human agents can the system be resilient to an increasing set of system demands. This panel will convey the work that they are doing and obstacles they are facing in the following areas: (1) demonstrating the critical importance of human-machine teaming, (2) hardening design patterns that result in successful human- machine teams, (3) designing and evaluating new automation solutions for their ability to team, and (4) ensuring that new automation solutions are implemented and adopted for risk-critical work.